2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Kuhn, Jens H; Adkins, Scott; Agwanda, Bernard R; Al Kubrusli, Rim; Alkhovsky, Sergey V; Amarasinghe, Gaya K; Avšič-Županc, Tatjana; Ayllón, María A; Bahl, Justin; Balkema-Buschmann, Anne; Ballinger, Matthew J; Basler, Christopher F; et al. (Archives of virology, 2021)
In March 2021, following the annual International Committee on Taxonomy of Viruses (ICTV) ratification vote on newly proposed taxa, the phylum Negarnaviricota was amended and emended. The phylum was expanded by four families (Aliusviridae, Crepuscuviridae, Myriaviridae, and Natareviridae), three subfamilies (Alpharhabdovirinae, Betarhabdovirinae, and Gammarhabdovirinae), 42 genera, and 200 species. Thirty-nine species were renamed and/or moved and seven species were abolished. This article presents the updated taxonomy of Negarnaviricota as now accepted by the ICTV.
Keywords: viry; Mononegavirales; Humans; Viruses; lidé